2021
DOI: 10.1108/jfm-01-2021-0002
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between narcissism, managerial overconfidence and comparability of financial statements of listed companies

Abstract: Purpose This study aims to investigate the impact of managerial narcissism and overconfidence on financial statements’ comparability. In other words, this paper seeks to answer the question of whether the personality characteristics of managers may affect the level of financial statements’ quality of commercial entities or not. Design/methodology/approach The research hypotheses are tested using a sample of 896 observations taken from the Tehran Stock Exchange and 245 observations from the Iraqi Stock Exchan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 55 publications
(61 reference statements)
0
6
0
3
Order By: Relevance
“…Secondly, the study introduces an empirical evidence on the factors that affect the level of environmental and ESGR. The study comprehensively evaluates the environmental pillar components by considering both the specific ED and overall ESG score [ 1 , 2 , 7 , 9 , 10 , [19] , [20] , [21] , [22] , [23] , [24] , [25] ]. Thirdly, the study assesses the effect of various board attributes and firms' specifics on the level of environmental and ESGR.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the study introduces an empirical evidence on the factors that affect the level of environmental and ESGR. The study comprehensively evaluates the environmental pillar components by considering both the specific ED and overall ESG score [ 1 , 2 , 7 , 9 , 10 , [19] , [20] , [21] , [22] , [23] , [24] , [25] ]. Thirdly, the study assesses the effect of various board attributes and firms' specifics on the level of environmental and ESGR.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to researchers who highlighted the bright side of narcissism, in this study, we contribute to research on CEO narcissism by analyzing its darker side in explaining CSI which, to date, has only scarcely being examined. For example, Almaleki et al (2021) found support for the negative impact of CEO narcissism on the quality of financial statements in a sample of 128 Iran firms from 2012 to 2018. They argue that narcissistic CEOs are likely to deliberately distort information, leading to a lack of disclosure of bad news to stakeholders and manipulating them for achieving support, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…ey used panel data regression to test the hypothesis. Almaleki et al [29] aimed to investigate the comparability between the impact of managerial pride and overconfidence on financial statements. Velte [30] showed the link between corporate governance and corporate financial misconduct.…”
Section: Related Workmentioning
confidence: 99%